Purification of Anthocyanins with o-Dihydroxy Arrangement by Sorption in Cationic Resins Charged with Fe(III) - Araceli Castañeda-Ovando; Carlos Andrés Galán-Vidal; Elizabeth Contreras-López; Ma. Elena Páez-Hernández (Journal of Chemistry)
In the present work, a new purification method of anthocyanins with o-dihydroxy arrangement is proposed. This method is based on a ligand-exchange mechanism, using a cationic exchange resin loaded with metallic ions in order to increase the affinity of the resin to the anthocyanin(s) with o-dihydroxy arrangement. This method was used to purify the main anthocyanin (cyanidin-3-glucoside; Cy-3-glc) from the anthocyanic methanolic extract of blue corn. The best sorption result was using Fe(III) in its ion form. The purification procedure begins with the formation of a metal-anthocyanin complex (Cy-3-glc-Fe) which was optimal at pH 5, followed by a NaOH 0.1 M elution process in order to eliminate anthocyanins without o-dihydroxy arrangement, sugars, and organic acids. Finally, the pure anthocyanin is obtained by adding HCl 0.1 M which breaks the metal-anthocyanin complex.